2014
DOI: 10.1002/adv.21477
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Die Geometry on Drawdown Force of Polypropylene at Capillary Extrusion

Abstract: Drawdown force, defined as the force needed to stretch a polymer melt uniaxially at capillary extrusion, is investigated using isotactic polypropylene. In this study, we focus on the effect of die geometry on the drawdown force. As similar to the swell ratio, which decreases with increasing die length, the drawdown force is found to increase with the die length. A prolonged residence time in a long die leads to the marked orientation. Consequently, crystallization occurs rapidly after passing through a long di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…The extrusion was performed at a constant shear rate of 14.6 s −1 (a constant piston speed), which corresponded to the lowest shear rate for the machine using the die with an l / d ratio of 10/1. A detailed description of the experimental procedure has been described elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…The extrusion was performed at a constant shear rate of 14.6 s −1 (a constant piston speed), which corresponded to the lowest shear rate for the machine using the die with an l / d ratio of 10/1. A detailed description of the experimental procedure has been described elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…Finally, Li et al revealed that the ionic interaction is responsible for the enhancement of melt strength, that is, the force required to stretch a molten polymer uniaxially at the non‐isothermal condition, for polypropylene . This phenomenon will be applicable because of strong demands in plastic industries …”
Section: Introductionmentioning
confidence: 99%
“…16 This phenomenon will be applicable because of strong demands in plastic industries. 17 Besides ionomers, solid (solvent-free) polymer electrolytes should be taken into consideration. Although most researches were performed using poly(ethylene oxide) and its copolymers in this field, in which Snyder et al reported the mechanical properties, 18 there have been a couple of researches on acrylate polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Such behavior was studied precisely by Wagner et al . and Seemork et al . Considering their research, we evaluated the drawdown force at two different draw ratios.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, a pronounced drawdown force is expected. However, there has been limited progress in studies of the influence of nucleating agents on drawdown force, with the exception of a few published reports …”
Section: Introductionmentioning
confidence: 99%